Evaluation of T-Cell Responses Against Shared Melanoma Associated Antigens and Predicted Neoantigens in Cutaneous Melanoma Patients Treated With the CSF-470 Allogeneic Cell Vaccine Plus BCG and GM-CSF - Podaza, Enrique; Carri, Ibel; Aris, Mariana; von Euw, Erika; Bravo, Alicia Inés; Blanco, Paula; Ortiz Wilczyñski, Juan Manuel; Koile, Daniel; Yankilevich, Patricio; Nielsen, Morten; Mordoh, José; Barrio, María Marcela (Frontiers in Immunology, 2020)
The CSF-470 vaccine consists of lethally-irradiated allogeneic cells derived from four cutaneous melanoma cell lines administered plus BCG and GM-CSF as adjuvants. In an adjuvant phase II study vs IFN-α2b, the vaccine significantly prolonged the distant metastasis-free survival (DMFS) of stages IIB-IIC-III melanoma patients with evidence of the induction of immune responses against vaccine cells. Here, we analyzed the antigens against which the immune response was induced, as well as the Thelper profile and lytic ability of immune cells after CSF-470 treatment. HLA-restricted peptides from tumor-associated antigens (TAAs) were selected from TANTIGEN database for 13 evaluable vaccinated patients. Besides, for patient #006 (pt#006), tumor somatic variants were identified by NGS and candidate neoAgs were selected by predicted HLA binding affinity and similarity between wild type (wt) and mutant peptides. The patient`s PBMC reactivity against HLA-restricted TAA-derived peptides was detected by IFNγ-ELISPOT, with a progressive increase in the number of spots throughout vaccination protocol. ELISPOT response correlated with DTH to CSF-470 vaccine cells. Early upregulation of GATA-3 and Foxp3 mRNA, as well as an increase in CD4+IL4+cells, was associated with a low DMFS. Also, IFNγ response against 9/73 predicted neoAgs was evidenced. In vitro, we verified that vaccine-stimulated T cells lysed autologous tumor cells. A progressive increase in the immune response against TAAs expressed in the vaccine and in the patient´s tumor was induced by CSF-470 vaccination. In pt#006, we demonstrated the immune recognition of the patient´s specific neoAgs, which emerged after vaccination. Thus, an initial response against shared TAAs could further stimulate an immune response against autologous tumor neoAgs.